FIVE COMPONENTS OF WORK MOTIVATION IN THE ACHIEVEMENT OF LECTURER PERFORMANCE - Wahyudi Wahyudi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
Achieving good work results requires hard efforts and support from many parties, especially in the field of lecturer performance. The reason is that in achieving educational performance (earning a doctorate), it takes financial adequacy, time, and good intellectual intelligence. Even in achieving research and service performance, it is not enough just to be able, but it is necessary to have a spirit of service in order to encourage change and prosperity for the surrounding community. Therefore, this research seeks to describe what things enable performance to be achieved in lecturers. The research method uses quantitative, where research data is obtained through questionnaires and interviews. While the data analysis used regression with descriptive narrative technique. The object of research is Pamulang University lecturer with the criteria of doctoral education and having a minimum functional position of Lector. The results of the research obtained information, that the greatest enthusiasm of lecturers in achieving performance is actualization. This is confirmed in the results of interviews, that the attachment of a lecturer's title fosters a spirit of wanting to show knowledge and capacity as a university teaching staff. Thus, various things are done, and no matter how big the sacrifices are made.